MUTUAL FUND PERFORMANCE IN A BULLISH MARKET DURING THE COVID-19 CRISIS - Yunqi Chen; Jia Sin Lim (The International Journal of Banking and Finance, 2024)
Active funds vs passive funds represent one of the most prominent investment decisions that ought to be undertaken by investors over the decades. Our paper seeks to offer an insight into the average performance of equity mutual funds during the period when there were roughly 70 ‘all-time-highs’ recorded by S&P 500 amid the COVID-19 health crisis. Additionally, our paper aims to explore the robustness and persistence of the explanatory powers of Morningstar sustainability globes, ratings from agencies and growth tilt during the health crisis. Our results indicated that the benchmark indexes seemed to dominate mutual funds in most cases during our sampling period. The ratings from Morningstar and/or Lipper together with growth investing appeared to be ideal elements to contemplate when making investment decisions during the COVID-19 health crisis.